Penerapan Keselamatan dan Kesehatan Kerja (K3) pada Atraksi Adventure Tourism di Kawasan Air Terjun Aling-Aling Sambangan - Rut Wiratami; Gde Indra Bhaskara (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2017)
Tourist safety is an important aspect in tourism activities and must have serious attention from the manager of a tourism destination. It is also one of tourist satisfaction over the service which further will imposes image of the destination around the world. Sambangan tourism village is one of the tourist destinations in North Bali which is currently popular to domestic and foreign tourists. There are two unique attractions become flagship attractions that are sliding and jumping. Along with the development of an increasing tourist visits since last few years, problems began appear. An accident even cause the loss of life and one of them is a local guide who made a living in that area. Therefore, this research is considered necessary and important in order to find out how the application of safety and health of work have been done so far. Data obtained through library studies, participatory observation and interviews with the determined informants.This research found that the safety and health aspects of work in Sambangan tourism village are still simple due to the limitations of funding and a lack of understanding in the health aspects so that the implementation of health and safety of workis done based on understanding. Therefore, in the future a further research is needed related to the health aspects of a medical, increasing of security aspects in the location of tourists attraction and also the attention and support from the government especially tourism department. Keywords: Safety and Healthy, Adventure Tourism, Attraction, Waterfall.